Osservazioni eterodosse sulla “situazione normativa” sottesa al caso giudiziario concernente le escort di un ex Presidente del Consiglio (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This work aims at describing the normative background underlying the issue of constitutionality of the statute n. 58/1958, art. 3, which foresees some behaviours, such as recruitment and aiding and abetting of prostitution, as a crime. The first part will be devoted to an exploration of the divergent perspectives of the Italian constitutional court decision (n. 141/2019) and the Bari Court of Appeal on self-determination and the so called “harm principle”, requiring an offense to have been committed against a given legal asset. The article then critically inquires the decision made by the Bari Court and, consequently, by the constitutional Court, of restricting the flaw of facts that have been considered relevant in the legal reasoning. On this basis, the article addresses the issue of which other constitutional values could have been taken into account in the occasion of the “incidental” constitutional review here discussed.
Keywords: harm principle; voluntary prostitution; dignity; duty of constitutional loyalty; constitutional review